PROFESSIONAL ZAKAT IN THE PERSPECTIVE OF MUHAMMADIYAH AND PERSATUAN ISLAM: A COMPARATIVE ANALYSIS - Amrullah; Rohman, Hilma Fanniar (Universitas Muhammadiyah Bengkulu, 2025)
Zakat, as a fundamental pillar of Islam, serves as a potential instrument for poverty alleviation. Among its contemporary applications is professional zakat, which remains a subject of debate due to the lack of explicit references in classical Islamic texts. This study aims to compare the perspectives of Muhammadiyah and Persatuan Islam (Persis) regarding the obligation of professional zakat and analyze the istinbath methodologies employed by both organizations. This research adopts a qualitative approach with a descriptive-analytical and comparative method. Data collection was conducted through documentary analysis, library research, and interviews with key figures from Muhammadiyah and Persis. The findings reveal that Muhammadiyah considers professional zakat obligatory, using a broad interpretation of zakat provisions and analogy with zakat on gold and silver. In contrast, Persis does not recognize professional zakat, arguing that zakat is an ibadah mahdhah that cannot be established without explicit textual evidence. Instead, Persis suggests mandatory infak on professional income without a fixed rate and nisab. These differences highlight the diversity of ijtihad and practice in Islamic social finance among muslims. However, both organizations agree on the necessity of social contributions from professional income, whether through zakat or infak